Management of infections for patient treated with ibrutinib in clinical practice - Baratè, Claudia; Scortechini, Ilaria; Ciofini, Sara; Picardi, Paola; Angeletti, Ilaria; Loscocco, Federica; Sanna, Alessandro; Isidori, Alessandro; Sportoletti, Paolo (Frontiers in Oncology, 2024)
Ibrutinib, a highly effective inhibitor of the Bruton tyrosine kinase, has significantly transformed the therapeutic approach in chronic lymphocytic leukemia (CLL). Despite these advancements, the disease continues to be characterized by immune dysfunction and increased susceptibility to infections, with mortality rates from infections showing no significant improvement over the past few decades. Therefore, timely prevention, recognition, and treatment of infections remains an important aspect of the standard management of a patient with CLL. A panel of hematologists with expertise in CLL met to discuss existing literature and clinical insights for the management of infectious in CLL undergoing ibrutinib treatment. Despite not being a fully comprehensive review on the topic, this work provides a set of practical recommendations that can serve as a guide to healthcare professionals who manage these patients in their daily clinical practice.